A self-tuning heuristic for the design of communication networks - ALABAŞ USLU, ÇİĞDEM (PALGRAVE MACMILLAN LTD, 2015)
This paper addresses the design of communication networks that has a large application area. The problem is to design a minimum cost network subject to a given reliability level. Complexity of the problem is twofold: (1) finding a minimum-cost network topology that every pair of nodes can communicate with each other and (2) computing overall reliability to provide the reliability constraint. Over the last two decades, metahemistic algorithms have been widely applied to solve this problem due to its NP-hardness. In this study, a self-tuning heuristic (STH), which is a new approach free from parameter tuning, is applied to the design of communication networks. Extensive computational results confirm that STH generates superior solutions to the problem in comparison to some well-known local search metaheuristics, and also more sophisticated metaheuristics proposed in the literature. The practical advantage of STH lies in both its effectiveness and simplicity in application to the design problem.
Keywords: network design; overall reliability; metaheuristics; parameter tuning; TABU SEARCH ALGORITHM; TOPOLOGICAL OPTIMIZATION; RELIABILITY OPTIMIZATION; GENETIC-ALGORITHM; RELIABLE NETWORKS; TERMINAL RELIABILITY; CONSTRAINTS; SUBJECT; SYSTEM; LAYOUT